2020
DOI: 10.1186/s12959-020-00233-y
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-dependent platelet dysfunction and its relevance to either mitochondrial ROS or cytosolic superoxide generation: a question about the quality and functional competence of long-stored platelets

Abstract: Background: Upon vascular damage, the exposed subendothelial matrix recruits circulating platelets to site of injury while inducing their firm adhesion mainly via GPVI-collagen interaction. GPVI also supports aggregatory and pro-coagulant functions in arterial shear rate even on the matrix other than collagen. Reactive oxygen species (ROS) modulate these stages of thrombosis; however augmented oxidant stress also disturbs platelet functions. Storeddependent platelet lesion is associated with the increasing lev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…ROS in platelets may be derived from NOX 1 and NOX 2 activation [ 26 ], which are positive regulators during agonist-induced platelet activation. On the other hand, ROS production during platelet storage has been described previously to cause PSLs, such as platelet receptor loss, granule release, and viability impairment [ 20 , 31 , 32 ]. Endogenous ROS produced during platelet storage could be a by-product of respiration chain [ 19 ], and accumulated ROS in stored platelets disturbs mitochondrial membrane potential, blocks ATP/ADP exchange translocase at the mitochondrial surface, then subsequently leads to apoptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS in platelets may be derived from NOX 1 and NOX 2 activation [ 26 ], which are positive regulators during agonist-induced platelet activation. On the other hand, ROS production during platelet storage has been described previously to cause PSLs, such as platelet receptor loss, granule release, and viability impairment [ 20 , 31 , 32 ]. Endogenous ROS produced during platelet storage could be a by-product of respiration chain [ 19 ], and accumulated ROS in stored platelets disturbs mitochondrial membrane potential, blocks ATP/ADP exchange translocase at the mitochondrial surface, then subsequently leads to apoptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have showed that PCs could alleviate oxidative stress, including in skeletal muscle contusion, gingival fibroblasts, and human spermatozoa, and ameliorate nephrotoxicity [ 19 ]. At the same time, platelets and their mitochondria may also be the sources of ROS [ 20 22 ]. Considering the role of mitochondrial transfer in reducing cell injury, it is worth considering whether the mitochondria released by platelets play a role in the process of platelet concentrates reducing oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 ROS are generated by NADPH oxidase, p66Shc oxidase, COX oxidase, and the mitochondrial respiratory chain. 11 Increased ROS levels can lead to platelet apoptosis, 12 activation, 13 loss of platelet adhesiveness and aggregation to reactive matrixes, 14 and a decline in platelet quality. 15 Notably, the concentrated platelets stored in an incubator and agitator undergo deleterious changes due to the physical interaction among the platelets and between them with the environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Factors that initiate PSL include storage duration and temperature, storage medium, container, and mode of agitation. , Both physical and chemical stimuli can affect platelet state, with excessive reactive oxygen species (ROS) accumulation being a primary cause for PSL. , ROS are generated by NADPH oxidase, p66Shc oxidase, COX oxidase, and the mitochondrial respiratory chain . Increased ROS levels can lead to platelet apoptosis, activation, loss of platelet adhesiveness and aggregation to reactive matrixes, and a decline in platelet quality . Notably, the concentrated platelets stored in an incubator and agitator undergo deleterious changes due to the physical interaction among the platelets and between them with the environment …”
Section: Introductionmentioning
confidence: 99%